Message - Awotona, Prof. Olanrewaju Rita-Marie (Universal Journal of Pharmaceutical Research, 2023)
As scientists we have all come through a season when the very essence of our beings has been tested by theories, hypothesis, scientific facts known and unknown. We have woken up to a brand-new world where the scientific experimental processes have had to be confirmed again and again. Its post Covid 19 and scientists have stayed strong and bold and convinced of their calling more now than ever before. It is obvious that many studies and investigations have been done by various countries which we will never know about, but many have also been highlighted and put out there so that the world can benefit. I have seen initiatives by African countries push ahead to use what they have and bring them up to the highest of standards. I have attended a meeting organized by WHO (2021) where countries in Africa presented their research as Covid waded along changing form, mutating, and giving scientists more unknowns to investigate. The countries showed progress in scientific research and reporting what progress they had made in coming up with future answers to Covid type infections. I was amazed at how each country had determinedly done so much in such a short time. Many nations had, in collaboration with others come up with natural remedies at various stages of experimentation, research, and clinical trials. I think that the facts of the season had begun to be revealed, that nations were beginning to take their destinies in their hands. Science in the last two years has been in great dispute and more than everbefore. It is more pertinent that journals be ready to publish scientific facts with good conscience. This is exactly what UJPR did in the last two years, focused on really important areas of science and especially all areas of pharmaceutical science. We have now come to a world where scientists must build on what others have done or are doing in other parts of the world as it is clear no one has all the answers. UJPR has helped connect scientists to one another and it would be interesting to see what relationships have developed through the years directly from the publication. Covid and all its attendant issues is ongoing and as answers to living healthy are sought for in the world, the part of the world where I come from, Africa are seeking answers from what they have. Some colleagues recently published a paper about the already available medicinal plants which are antiviral, and which could readily be investigated for activity against Covid. This type of publication serves as base information for others to work with and use. Journals in this time will serve as a global information center.UJPR has not failed in its duty to make sure that the highest standard of scientific information has been released over the past years. The quality keeps on improving and content has increased. I encourage everyone to keep working hard and supporting the editorial team of UJPR. The Journal will keep progressing and we have enough space at the top!! I keep on congratulating UJPR for taking on the challenge of giving out factual scientific information and being credible. I continue to look forward to the next issues as we build the mountain of knowledge of the world.